Effects of Surfactants on High Regularity of 3D Porous Nickel for Zn2+ Adsorption Application. (18th March 2014) - Guo, Xiaogang; Li, Xueming; Zheng, Yonghong; Lai, Chuan; Li, Wulin; Luo, Binbin; Zhang, Daixiong
Abstract : Three-dimensional porous nickel (3D-PN) film with large specific surface area (A s ) and high porosity has been successfully prepared by hydrogen bubble dynamic template (HBDT) method. This work presents the effects of PEG 10000 and 1, 4-butynediol as new additive combination on surface morphology of the PN film. Meanwhile, the application of 3D-PN in Zn 2+ adsorption was preliminarily investigated in the paper. The surface area is determined as large as 166.7 cm 2 /mg and the porosity is 0.762 when the concentration of PEG 10000 and 1, 4-butynediol was 0.3 g/100 mL and 0.1 g/100 mL, respectively. The adsorption capacity (Q t and Q (%)) of PN for Zn 2+ is observed to be 9.145 mg/g and 0.691 for Zn(NO3 )2 ·6H2 O. The morphology and the microstructure, the product formation, the A s the concentration of the metal ions were characterized by scanning electron microscopy (SEM), X-ray powder diffraction (XRD), electrochemical impedance spectroscopy (EIS), and atomic absorption spectrometry (AAS), respectively.